Respuesta :

uhssma
the equation is balanced by the 3's on both sides so that cancels out. we are left with:
x^2-6x=0
we take out an x, leaving us with:
x(x-6)=0
we know that to find the solution [ or "zero's", ] we must set "x"=0, and "x-6"=0.
the solutions are: x=0 and 6.
hope that helped, xx

Answer:

x = 0

x = 6

Step-by-step explanation:

x² - 6x + 3 = 3

x² - 6x + 3 - 3 = 0

x² - 6x = 0

(x - 6)(x + 0) = 0

Two separate equations

x - 6 = 0

x + 0 = 0

x - 6 = 0

x - 6 + 6 = 0 + 6

x = 6

x + 0 = 0

x + 0 - 0 = 0 - 0

x = 0

ACCESS MORE